Evaluation of Imidacloprid Induced Changes in Thyroid Gland and its Amelioration with Withania somnifera in Wistar Rats - Samala, Soujanya; Mekala, Lakshman; Doppalapudi , Madhuri; Alla, Gopala Reddy; Rao, Rama (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was conducted on a total of 48 female Wistar rats divided into four groups, each containing 12 rats. Group 1 was control, group 2 was imidacloprid control, group 3 was Withania somnifera control and group 4 was administered with both imidacloprid and Withania somnifera. The rats of group 3 and 4 were subjected to oral treatment of Withania somnifera (1 gm/kg feed) for a period of 30 days to measure the protective effect against thyroid toxicity induced by imidacloprid (30 mg/kg body weight/day for 30 days). Hormonal assays showed a significant (p<0.05) rise in thyroid stimulating hormone and fall in triidothyronine and thyroxine in imidacloprid administered rats when compared to control. No gross lesions were noticed in thyroid gland. Group 2 thyroid gland sections revealed congestion, degenerated thyroid follicles with loss of colloid substance, increase in inter-follicular space, atropic follicles, fibrosis, pyknotic nuclei, detachment of follicular epithelial cells, increase in number of micro-follicles and proliferation of follicular epithelium towards lumen. Electron microscopy of thyroid gland from group 2 rats revealed significant pathological changes. The degree of lesions was minimal in group 4 rats when compared to group 2 rats. These results indicate that Withania somnifera is beneficial in ameliorating the imidacloprid induced thyroid toxicity in rats.